Counseling on Safe Snacks for School Children in Indonesia and Malaysia - Setiawan, Ari; Muflihah Isnawati; Rauza Sukma Rita; Mulono Apriyanto; Arum Putri Rahayu (IMPACTS: International Journal of Empowerment and Community Services, 2025)
ABSTRACT Purpose The aim of community service are: Providing provisions and insight to teachers and students on the importance of healthy food types for students, Providing insight into the dangers of indiscriminate snacking and unhealthy food, Providing insight into safe and healthy snack behavior, Increasing awareness of school residents to jointly choose healthy snacks and provide access and facilities for healthy snacks. Methods - This community service activity is carried out in the form of counseling / training containing material both online and offline to increase understanding of the importance of choosing healthy and nutritious snacks for school children. Training/counseling is a method or effort made by certain parties to increase the understanding of teachers or students by providing certain material in a planned and programmed manner. The stages of this training/counselling adapt the conceptual model. Health counseling is an activity to provide health education that has a method by disseminating messages and instilling confidence. So that people are not only aware, know, and understand but are also able to do or follow recommendations related to the health information Result and discussions - This service activity was responded well by both teachers and students because it proved to have a significant impact. Through counseling activities related to safe snacks for children, teachers and students gain additional knowledge and information related to healthy and nutritious snacks. In addition, they can find out the dangers of careless snacking. Both teachers and students felt happy and satisfied with this activity. Increasing awareness in choosing healthy snacks and taking preventive efforts and real steps to provide healthy snacks for students at school.Conclusion - Community service activities went well, smoothly and received a good response as seen from the participation of all teachers, students and partners. Teachers and students were very enthusiastic during the service and felt happy because they had increased their knowledge about safe types of snacks. This service also succeeded in opening the insights of teachers and students to be careful with the snacks available and try to bring provisions on certain days or optimize the role of the school canteen.